Recyclable Hypervalent Iodine Reagents in Modern Organic Synthesis - Rimi, Rimi; Soni, Sakshi; Uttam, Bhawna; China, Hideyasu; Dohi, Toshifumi; Zhdankin, Viktor V; Kumar, Ravi (Synthesis, 2022)
Hypervalent iodine (HVI) reagents have gained much attention as versatile oxidants because of their low toxicity, mild reactivity, easy handling, and availability. Despite their unique reactivity and other advantageous properties, stoichiometric HVI reagents are associated with the disadvantage of generating non-recyclable iodoarenes as waste/co-products. To overcome these drawbacks, the syntheses and utilization of various recyclable hypervalent iodine reagents have been established in recent years. This review summarizes the development of various recyclable non-polymeric, polymer-supported, ionic-liquid-supported, and metal–organic framework (MOF)-hybridized HVI reagents.1 Introduction2 Polymer-Supported Hypervalent Iodine Reagents2.1 Polymer-Supported Hypervalent Iodine(III) Reagents2.2 Polymer-Supported Hypervalent Iodine(V) Reagents3 Non-Polymeric Recyclable Hypervalent Iodine Reagents3.1 Non-Polymeric Recyclable Hypervalent Iodine(III) Reagents3.2 Recyclable Non-Polymeric Hypervalent Iodine(V) Reagents3.3 Fluorous Hypervalent Iodine Reagents4 Ionic-Liquid/Ion-Supported Hypervalent Iodine Reagents5 Metal–Organic Framework (MOF)-Hybridized Hypervalent Iodine Reagents6 Conclusion
Keywords: hypervalent iodine; recyclable reagents; polymer-supported; non-polymeric; ionic-liquid-supported; MOF hybrid